Age- and temperature-related pupal eye colour changes in various tephritid fruit fly species with a view to optimizing irradiation timing. (19th August 2014) - Resilva, Sotero S.; Pereira, Rui
Abstract : The application of the sterile insect technique to fruit flies involves the mass-production of the pest insects using an artificial diet, irradiation during a narrow time window at the late pupal or early imaginal stage to inhibit reproduction without affecting reproductive capacity, and then release into the target area where the sterile insects compete reproductively with their wild counterparts. The timing of irradiation is important to enable the release of males that are sterile but of good quality and exhibit an acceptable sexual performance. In this study, we examined the pupal development of 12 tephritid (Diptera: Tephritidae) species: Anastrepha fraterculus (Wiedemann), A. ludens (Loew), A. obliqua (Macquart), A. serpentina (Wiedemann), Bactrocera cucurbitae (Coquillett), B. dorsalis (Hendel), B. invadens (Drew, Tsuruta & White), B. oleae (Rossi), B. philippinensis (Drew & Hancock), B. tryoni (Froggatt), B. zonata (Saunders) and Ceratitis capitata (Wiedemann). The insects were reared at various temperatures, in the laboratory (15–28 °C) and under fluctuating natural conditions (20–35 °C). The gradual colour changes of the insect eyes during metamorphosis were observed and photographed, measuring the specific eye colour parameters of each species and matching them with the colour scale of the Munsell Soil Color Charts. The duration of pupal development and the time to emergence in Anastrepha species were longer than those in C. capitata and Bactrocera species at all the holding temperatures. The data obtained can be used by mass-rearing facilities to manage pupal holding conditions and as indicators for optimizing the timing of irradiation.